Excited States of a Magnetic Polaron in a Quantum Well - K. Jayakumar; P. Nithiananthi (Журнал нано- та електронної фізики)
The effect of magnetic field on the donor binding and spin polaronic shift of a donor in some low lying excited in a semimagnetic Quantum Well has been investigated in the effective mass approximation using the variational principle including the effect of non-parabolicity of the conduction band. The results are presented and discussed.